2022
DOI: 10.1186/s12645-022-00141-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and application of cisplatin-loaded mesoporous magnetic nanobiocomposite: a novel approach to smart cervical cancer chemotherapy

Abstract: There are significant challenges in developing drug carriers for therapeutic perspective. We have investigated a novel nanocarrier system, based on combining functionalized magnetic nanocomposite with Metal–Organic Frameworks (MOFs). Magnetic nanoparticles modified using biocompatible copolymers may be suitable for delivering hydrophobic drugs, such as cisplatin. Furthermore, compared to polymeric nanocarriers, nanocomposite constructed from zeolitic imidazolate framework-8 (ZIF-8) have demonstrated better dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Fe 3 O 4 @SiO 2 @nanochi/FA‐ cis group (treated with Fe 3 O 4 @SiO 2 @NChi/FA‐ cis administered the same as group II). Time period and dose selection were selected based on the previous studies 43,44,66 . When the tumor volume reached 70–100 mm 3 , the treatment was started and continued during the study 67 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fe 3 O 4 @SiO 2 @nanochi/FA‐ cis group (treated with Fe 3 O 4 @SiO 2 @NChi/FA‐ cis administered the same as group II). Time period and dose selection were selected based on the previous studies 43,44,66 . When the tumor volume reached 70–100 mm 3 , the treatment was started and continued during the study 67 .…”
Section: Methodsmentioning
confidence: 99%
“…Also, there was a pH‐dependent release of cisplatin in both A549 and MCF‐7 cell lines 42 . Furthermore, our recent studies have shown that magnetic MOF nanobio‐composites 43 and Mxene‐magnetic nanosheets are capable of carrying cisplatin 44 …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, it is possible to limit the toxicity of a drug by selective activation, which would reduce or eliminate any adverse effects and invasiveness ( Nestler and Lüscher, 2019 ). In addition, several nanomaterials have been demonstrated to possess unique therapeutic potential, such as two-dimensional nanomaterials ( Gong et al, 2017b ; 2017a ; Darroudi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%